Exploring the English Language Needs of EAP Students of Humanities and Social Sciences in Iran: A Triangulated Approach - Amir Zand-Moghadam (Issues in Language Teaching, 2018)
Given the fact that few studies have investigated the English language needs of EAP students in Iran, the present study was an attempt to analyze the needs of Iranian EAP learners of Humanities and Social Sciences. To this end, 114 EAP learners at different educational levels (BA, MA, and PhD) and with different English proficiency levels (elementary, intermediate, and advanced) were asked to provide their responses to a questionnaire. Moreover, ten EAP learners and eight EAP instructors were asked to write narratives about their experiences in EAP courses. Their narratives were then analyzed based on Strauss and Corbin's (1998) systematic approach. The results revealed that the EAP courses did not pay the deserved attention to writing, speaking, and listening skills, while the coverage of the sub-skills (grammar and vocabulary) was successful. Moreover, it was revealed that the EAP textbooks were insufficient in terms of the inclusion of language skills, community-specific cultural issues and conventions, and the topical knowledge. The analysis of the EAP learners’ needs also showed that not all interaction types happened in the EAP courses. Furthermore, the analysis of the narratives of EAP learners and EAP instructors indicated that the EAP curriculum, EAP textbooks and also EAP assessment should include the four language skills, provide a communicative venue for EAP learners to practice their disciplinary issues, and design communicative materials. It can be concluded that the current EAP curriculum needs revision to fulfill the EAP learners’ present and target situation needs.